Cabo Verde : Request for an Extension of the Program Under the Policy Coordination Instrument. (IMF Staff Country Reports; Country Report, 2021)
Cabo Verde's Policy Coordination Instrument (PCI) is due to expire on January 15, 2021. In the attached letter, the authorities request its extension through March 31, 2021. Cabo Verde's 18-month PCI was approved by the Executive Board on July 15, 2019. Two reviews have been concluded, with the second delayed by over a month due to additional work generated by the impact of COVID-19 for staff and for the authorities. The requested extension will provide additional time to conclude the third and final review under the PCI.